Flowering and fruiting phenology of Paphiopedilum glaucophyllum J.J. Sm. Var. glaucophyllum (Biodiversitas Journal of Biological Diversity, 2006)
Paphiopedilum glaucophyllum J.J.Sm. var. Glaucophyllum is one of the endemic orchid from east java categorized as rare plant in Indonesia. The most prominent properties of this species is on the flower which have an purple labelum in sac shaped. The flowering time of this slipper orchids is undefinitely, so they can blossoming out every season of the year. The objective of this research was to observe the flowering time from blossoming out untill emerging fruit of the slipper orchid. The observation of flowering phenology was began from the first flower bud initiation until developing fruit. The observation cover from measurement of lenght and width of flower bud primordialfollowed by fruit development and characterised the physical change during development. The result showed the average period of flowering phenology from the beginning until emerging fruit in 62 days. The maturation of fruit take for 120 until 130 days calculated from the beginning of pollination.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Flowering phenology, emerging fruit, Paphiopedilum glaucophyllum var. glaucophyllum